Author reply: Do Tunisians have a European ancestry?. Issue 1 (8th July 2021) - Stanojevic, Sanja; Hall, Graham L.; Filipow, Nicole; Ruppel, Gregg; Okitika, Tolu; Thompson, Bruce; Kirkby, Jane; Steenbruggen, Irene; Cooper, Brendan G.
H. Ben Saad's summary of the Tunisian population and use of the "European" label in our recent Global Lung Function Initiative (GLI) lung volume paper [1] highlights that we live in a diverse world and using a limited number of labels to define populations and ancestral groups is fraught with bias and historical artefact. We recognise that no single reference equation for lung function outcomes can be generalisable globally. Until we have more comprehensive data from all regions in the world, we must be careful not to apply GLI equations indiscriminately. It is imperative that we continue to conduct research to better understand how ancestry, as well as social and environmental determinants, impacts lung health. The GLI is reviewing the factors that explain observed population differences and will work towards developing more broadly applicable reference equations in the future. Until we have more comprehensive data from all regions in the world, we must be careful not to apply GLI equations indiscriminately https://bit.ly/3g1r9Q5